Effect of ultrasound treatment on quality parameters and health promoting activity of fish protein hydrolysates extracted from side streams of Atlantic mackerel (Scomber scombrus) - Cropotova, Janna; Kvangarsnes, Kristine; Rustad, Turid; Stangeland, Janne; Roda, Gabriella; Fanzaga, Melissa; Bartolomei, Martina; Lammi, Carmen (Frontiers in Nutrition, 2024)
Fish protein hydrolysates (FPH) obtained by enzymatic hydrolysis allows for smart valorization of fish side streams. However, further treatments are normally needed to enhance bioactive and functional properties of FPH. At present, the commonly used methods to improve functional properties of FPH include chemical and enzymatic modification. Chemical treatments often cause environmental problems, while the enzymatic modification method requires the use of quite expensive enzymes. In recent years, emerging technologies such as ultrasound treatment (US-treatment) have shown great potential in protein modification with high efficiency and safety, low energy consumption, and low nutritional destructiveness. In this study, ultrasound treatments were applied to FPH extracted from Atlantic mackerel (Scomber scombrus) side streams to improve their quality. The effect of three different treatments of 300W, 450W and 600W for 10 minutes on the physicochemical, structural, and functional characteristics of FPH, were examined. The results have shown that with an increase in ultrasound power, the protein solubility of FPH increased linearly, and the changes were significant for all US-treated samples compared to control. US-treatment significantly increased degree of hydrolysis of FPH treated with 450W and 600W compared to control. The carbonyl content of FPH increased (significantly for 450W and 600W), while thiol groups decreased (significantly for 300W and 450W). This indicated that some US-treatments induced oxidation of FPH, however the values of the protein oxidation were low. Amino acid composition of FPH revealed that US-treatment increased the proportion of essential amino acids in the sample treated with 300W and 450W, but it was not significant. After the US-treatment, all FPH samples became lighter and less yellowish and reddish, which suggest potentially higher attractiveness to consumers. In addition, the in vitro antioxidant activity was assessed using the DPPH, FRAP, and ABTS assays and the cell-free dipeptidyl peptidase IV (DPP-IV) inhibitory activity was also measured. Moreover, these biological activities were measured at cellular level utilizing human intestinal Caco-2 cells. Specifically, the FPH capacity to lower H2O2-induced reactive oxygen species (ROS) and lipid peroxidation levels was used to measure its antioxidant activity. The findings suggest that mackerel hydrolysates could find use as ingredients for promoting health.